1288 Colorectal Cancer Surgery Service Provision During The COVID-19 Pandemic: An Assessment of a Single Trust. (12th October 2021) - Hanna, J; Khoory, C; Manu, N; Clifford, R; Fowler, H; Fok, M; Vimalachandran, D
Abstract: Aim: Post-operative pulmonary complications in perioperative SARS-CoV-2 infection are associated with significant morbidity and mortality. To maintain a safe cancer service, the Countess of Chester Hospital adopted "Cold-site" operating and maintained ERAS principles for patients undergoing elective colorectal cancer surgery during the pandemic. A comparative assessment of service was undertaken for benchmarking purposes. Method: A comparative retrospective audit was undertaken of consecutive patients undergoing elective colorectal cancer surgery from June to November 2019 and compared to June to November 2020. The Somerset Cancer Registry and electronic medical case records were used to obtain the dataset. Outcomes measured were approach to surgery; stoma rate; length of stay; level of care required; post-operative complications (>Clavien-Dindo 2) and survival at 30 days. Mann-Whitney U test and Chi-squared were used for analysis. Results: There were 33 and 24 elective colorectal cancer operations in 2019 and 2020 respectively. There was no difference in the median age (64:69; p = 0.3) or ASA grade (p = 0.9). The median length of stay was 5 and 4 days respectively (p = 0.3). There was a 32.2% reduction in laparoscopic approach to surgery in 2020 (69.7% vs 37.5%; p = 0.02). There was no difference in the stoma rate (p = 0.9), post-operative complication rate (p = 0.7), ITU admission rate (p = 0.3), length of ITU stay (p = 0.6) and 30-day mortality rates (p = 0.4). Conclusions: "Cold-site" operating allows robust ERAS care to be adopted to ensure comparative outcomes for patients undergoing colorectal cancer surgery and was associated with a non-significant trend to shorter hospital stay during the COVID-19 pandemic.